2018
DOI: 10.3390/ijgi7070263
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Creative Spaces in Omaha, NE: Resident Perceptions versus Creative Firm Locations

Abstract: Abstract:In an era increasingly shaped by automation and globalization, industries that rely on creativity, innovation, and knowledge-generation are considered key drivers of economic growth in the U.S. and other advanced capitalist economies. This study examines the spatial distribution of creative firms and how they might align with perceptions of creativity in Omaha, Nebraska, a mid-sized U.S. urban area. Utilizing a survey, participant mapping exercise, and geospatial analyses, the primary goal was to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…The author contends that this pushes creative or cultural workers to develop a large web of relatively weak professional ties, which, presumably, could be accomplished to greater effect in compact and diverse urban environments. In agreement with this theory, both Spencer (2015) and Bereitschaft (2018a) observed that creative/cultural firms were more likely to be found in dense urban environments, while science/technology firms exhibited a preference for the suburbs. Other studies have examined the clustering of 'creative' industry firms, noting in detail the role the built environment plays in facilitating interactions both within and across industries (Costa & Lopes, 2015;Durmaz, 2015;Rantisi & Leslie, 2010;Martins, 2015).…”
Section: Background: Walkability and Innovationmentioning
confidence: 65%
“…The author contends that this pushes creative or cultural workers to develop a large web of relatively weak professional ties, which, presumably, could be accomplished to greater effect in compact and diverse urban environments. In agreement with this theory, both Spencer (2015) and Bereitschaft (2018a) observed that creative/cultural firms were more likely to be found in dense urban environments, while science/technology firms exhibited a preference for the suburbs. Other studies have examined the clustering of 'creative' industry firms, noting in detail the role the built environment plays in facilitating interactions both within and across industries (Costa & Lopes, 2015;Durmaz, 2015;Rantisi & Leslie, 2010;Martins, 2015).…”
Section: Background: Walkability and Innovationmentioning
confidence: 65%
“…The limit values for the criteria are data-driven, following the general recommendation (stated in [81]) of analysing at least five studies to identify the influence of the given factor (variable). When setting the limit value, possible values (5,7,10,15) were validated by statistical analysis (evaluation of data distribution) with the aim of high discrimination and reliability of the results. The limit value of five studies yielded the discrimination of about 30% (portion of factors meeting the requirement), while the other possible limit values considerably lowered the numbers of "proven" factors.…”
Section: Evaluation Of the Provability Of Factorsmentioning
confidence: 99%
“…The aforementioned alternative perspectives, among others, allow different ways of collecting and evaluating data about mental maps. If we want to recall spatial information from memory, we can use various methods, such as sketching a map [7][8][9][10], modelling the Earth's surface [11] or interviewing [12][13][14][15] (see more in [2]). The sketch map method allows an individual's mental map to be understood more completely (in contrast to other methods), because it also allows for a metric evaluation of the quality of the spatial relations between objects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Matei, Ball-Rokeach, and Qiu 2001;Curtis et al 2014Curtis et al , 2019, the concentration of "creative industry" (e.g. Bereitschaft 2018;Brennan-Horley and Gibson 2009;Brennan-Horley et al 2010), access to jobs (e.g. Boschmann 2011), residents' physical activity (e.g.…”
Section: Sketch Mappingmentioning
confidence: 99%